2017
DOI: 10.1007/s40263-017-0417-0
|View full text |Cite|
|
Sign up to set email alerts
|

Adherence and Persistence Across Antidepressant Therapeutic Classes: A Retrospective Claims Analysis Among Insured US Patients with Major Depressive Disorder (MDD)

Abstract: BackgroundAdherence and persistence to therapy, or how well a patient follows provider directions on frequency and time to discontinuation of prescribed medications, is associated with positive health outcomes, including decreased healthcare costs and patient mortality. A clear literature gap exists assessing adherence and persistence to antidepressants (ADs) in the major depressive disorder (MDD) population at clinically relevant time points and at the therapeutic class level.ObjectiveThis study assessed adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 32 publications
5
67
0
4
Order By: Relevance
“…SNRIs was proved to have a higher response rate and less remission, especially for treating depression‐associated neuropathic pain and other pain, as we could see in our results that neurological symptoms and headache were both risk factors. These two results were consistent with a previous study that adherence of SNRIs was better than SSRIs but TCAs was worse . Surprisingly, “not treated by another class of medicine except for anti‐depressants in the current episode” was a risk factor for quitting medication.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…SNRIs was proved to have a higher response rate and less remission, especially for treating depression‐associated neuropathic pain and other pain, as we could see in our results that neurological symptoms and headache were both risk factors. These two results were consistent with a previous study that adherence of SNRIs was better than SSRIs but TCAs was worse . Surprisingly, “not treated by another class of medicine except for anti‐depressants in the current episode” was a risk factor for quitting medication.…”
Section: Discussionsupporting
confidence: 62%
“…28 While "SNRI-treated first episode" was a protecting factor. SNRIs was proved to have a higher response rate and less remission, 29 especially for treating depression-associated neuropathic pain and other pain, 30 as we could see in our results that neurological symptoms and headache were both risk factors. These two results were consistent with a previous study that adherence of SNRIs was better than SSRIs but TCAs was worse.…”
Section: Treatment Factorssupporting
confidence: 63%
“…With respect to the uncertainty around the mean estimate of the state‐transition probabilities and risk ratio, the beta and lognormal distribution were adopted, as shown in Table …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the health utility of the dropout state was calculated by the following formula: 0.25emUdrop=Udep×()1Prem+Urem×Prem, where U drop , U dep , U rem , and P rem represent the health utility of the dropout state, depression state, and remitted state, and the probability of patients being remitted without treatment among all dropout patients, respectively. Here, the probability was estimated as 0.31 on the basis of the results from Keyloun et al and Sawada et al Hence, the means of the health utilities for dropouts were: 0.45 for severe depression and 0.66 for moderate depression. With respect to health‐related utility, the beta distribution was supposed for the distribution of health‐related utility scores.…”
Section: Methodsmentioning
confidence: 99%
“…More inviting is the growing array of large centralized databases collected and stored away from and independent of sites of actual clinical practice, affording the opportunity for rapid review and analysis of a wealth of de-identified information on hundreds or thousands of patients. Key examples of such data repositories are those derived from insurance claims and, the subject of a major report in the current issue of CNS Drugs [1], those containing longitudinal pharmacy records of prescribed medications.…”
mentioning
confidence: 99%